Tradisi Masyarakat Muslim Dalam Membagi Harta Warisan Secara Kekeluargaan (Studi Di Kecamatan Jekan Raya Kota Palangka Raya) - Utami, Utami (Jurnal Studi Agama dan Masyarakat, 2016)
The background of the tradition of the muslim community in dividing the inheritance amicably was due to advice from one or more of the heirs which the most dominant in the division of inheritance,Â  because inheritance heir of inadequate if distributed with the way faraid, in addition there are also which based on the message ofÂ  inheritor before died to the heirs to share of inheritance the amicably. The purpose of this research was the tradition of the muslim community in dividing. This research uses descriptive qualitative approximation is collect and describe the data and facts matching in with situation which to exist at field and that obtained from the result of observation, interview and documentation. The result of this research demonstrate that The practice of implementation of the division of inheritance traditions amicably, there are two i.e. ways the division which done with the way agreement the family and the based to testament of the inheritor in moment still living, whereas the impact of the division of inheritance with the way amicably which done based on the message of inheritor before died to the heirs to divide of inheritance with the way amicably it is the positively impact.